Konservasi Preventif Karya Seni Lukis bagi Mahasiswa Seni - Irma Damajanti (Journal of Visual Art and Design, 2007)
The book of "The Introduction of Preventive Conservation on Painting for Visual Art Students" explains how to apply preventive conservation techniques for objects of culture and collections, especially paintings. It is said that preventive conservation optimizes environmental conditions to which objects and collections are housed.  By controlling light and ultraviolet radiation, humidity and temperature, biological pets, dust and pollutants, we can prevent damages and decays of the paintings.  In addition, preventive conservation also means in ensuring that good handling, transportation, storage and displaying techniques are used at all times.  Thus, applying preventive methods can prolong and protect the life of artworks for the future. Yet, although the Introduction of Preventive Conservation on Painting provides information on how to give care of paintings as objects of culture and collections, it is important to understand that all except the simplest conservation treatments should be taken by trained conservators. Thus, active conservation treatment is a response skill to the damaging process of cultural artifacts, a highly skilled field that requires extensive knowledge on the use of chemicals and rigorous technical procedures.